2010
DOI: 10.1016/j.snb.2010.07.059
|View full text |Cite
|
Sign up to set email alerts
|

A transparent TMPyP/TiO2 composite thin film as an HCl sensitive optochemical gas sensor

Abstract: a b s t r a c tTetracationic porphyrin (TMPyP) molecules were incorporated into an optically transparent TiO 2 thin film, prepared by Glancing Angle Physical Vapour Deposition (GAPVD), by simple infiltration (at pH 6.4). The preparation of optically transparent TMPyP/TiO 2 composite thin films provides a method for the integration of the porphyrin molecules into photonic devices for direct monitoring of gases. Previously, UV-visible and fluorescence spectral techniques have been used to study the reversible pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 16 publications
3
43
0
Order By: Relevance
“…Modeling the OAD thin film microstructure and growth by Monte Carlo (MC) simulation and other numerical methods has been carried out to better understand the evolution of porosity as a function of the deposition angle [93,228], with Suzuki et al [62] deducing that evaporated OAD thin films should present a maximum surface area at an evaporation angle of 70°. Interestingly, experiments exploring different adsorptions from the liquid phase have confirmed a maximum surface adsorption capacity at this ''magic deposition angle" [63,[229][230][231].…”
Section: Porosity and Adsorption Propertiesmentioning
confidence: 84%
See 2 more Smart Citations
“…Modeling the OAD thin film microstructure and growth by Monte Carlo (MC) simulation and other numerical methods has been carried out to better understand the evolution of porosity as a function of the deposition angle [93,228], with Suzuki et al [62] deducing that evaporated OAD thin films should present a maximum surface area at an evaporation angle of 70°. Interestingly, experiments exploring different adsorptions from the liquid phase have confirmed a maximum surface adsorption capacity at this ''magic deposition angle" [63,[229][230][231].…”
Section: Porosity and Adsorption Propertiesmentioning
confidence: 84%
“…In the liquid phase of a photonic sensor incorporating dye molecules in transparent OAD thin films (see Section 5.4), we have observed that the pH of the medium greatly modifies the adsorption capacity of cationic or anionic organic molecules from the rhodamine and porphirine families [229,230,[242][243][244][245][246][247][248]. To account for this pH dependent behavior, we have used the classical zero point of charge concept (zpc), which is widely used in colloidal chemistry [249].…”
Section: Porosity and Adsorption Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, porphyrins in films and membrans are widely used for sensing of gases: e.g. oxygen [28,49,50], nitrogen oxides [28,51,52,53], carbon monoxide [52], carbon dioxide [54], hydrogen chloride [55], and ammonia [56]. The simultaneous determination of oxygen and carbon dioxide [54], oxygen and temperature [49] as well as oxygen and hydrogen peroxide [50] can be implemented too.…”
Section: Analytical Applications Of Porphyrinsmentioning
confidence: 99%
“…One of these undesirable compounds, whose use is nowadays strictly regulated in many countries, is hydrogen chloride (HCl), a residual product from some industrial processes that interacts with the environment and natural biosystems. Optochemical sensing of HCl vapors can be accomplished through the use of organic dyes that change their absorption properties under the action of this acid at room temperature, with sensitivity at the ppm level or less .…”
Section: Introductionmentioning
confidence: 99%